Water Resources Sector Strategy : Strategic Directions for World Bank Engagement - World Bank (Washington, DC, 2013)
In 1993 the Board of the World Bank endorsed a Water Resources Management Policy Paper (WRMPP). In that paper, and in this Strategy, water resources management comprises the institutional framework (legal, regulatory and organizational roles), management instruments (regulatory and financial), and the development, maintenance and operation of infrastructure (including water storage structures and conveyance, wastewater treatment, and watershed protection). The 1993 Policy Paper reflected the broad global consensus that was forged during the Rio Earth Summit of 1992. This consensus stated that modern water resources management should be based on three fundamental principles (known as the Dublin Principles). First is the ecological principle which argues that independent management of water by different water-using sectors is not appropriate, that the river basin should be the unit of analysis, that land and water need to be managed together and that much greater attention needs to be paid to the environment. Second is the institutional principle, which argues that water resources management is best done when all stakeholders participate, including the state, the private sector and civil society; that women need to be included; and that resource management should respect the principle of subsidiarity, with actions taken at the lowest appropriate level. Third is the instrument principle, which argues that water is a scarce resource and that greater use needs to be made of incentives and economic principles in improving allocation and enhancing quality.